Experimental and theoretical study of bidirectional photoswitching behavior of 5, 5′-diphenylhydantoin Schiff bases: synthesis, crystal structure and kinetic approaches. (25th August 2020) - Todorov, Petar; Georgieva, Stela; Peneva, Petia; Rusew, Rusi; Shivachev, Boris; Georgiev, Anton
Abstract : Herein, the synthesis and characterization of four novel 5, 5′-diphenylhydantoin Schiff bases containing different aromatic species are presented. Abstract : Herein, the synthesis and characterization of four novel 5, 5′-diphenylhydantoin Schiff bases containing different aromatic species are presented. Their structure–property relationship was studied by X-ray, optical and electrochemical methods as well as DFT calculations in terms of their E / Z photoisomerization and enol/keto phototaumerization. The big challenge in photoinduced motion is achieving control and stability over the two isomers. Solvent-driven bidirectional photoswitching behavior was studied in nonpolar 1, 4-dioxane and polar aprotic DMF. T-type photochromism in 1, 4-DOX and opposite behavior in DMF as P-type switches (bistable system) were observed. The obtained results lead to a conclusion that by variation of the solvent environment a direct control over the bidirectional switching behaviour from T-type to P-type can be achieved.